Kompatibilitas pada Persilangan Self Anggrek Dendrobium aphyllum - Welsiliana, Welsiliana; Dewi, Ni Putu Yuni Astriani; Makin, Florian M. P. R.; Wiguna, Gede Arya; Jefriyanto, Wilson (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Indonesia has a very rich biodiversity, one of which is the genetic diversity of orchid species. Preservation and propagation of orchids are always carried out because they have many benefits and the availability of orchid germplasm is always there. Therefore, this research aims to test the compatibility of the Dendrobium aphyllum orchid through self-crossing. The crossing method used is self-crossing, namely crossing flowers in the same flower arrangement. The cross begins by taking 100 flowers, then each flower takes its pollinia and inserts it into the stigma hole of the other flower. After the crossing is carried out, observations are continued once a week and if fruit is successful then observations are carried out once a month. The results of the research showed that the percentage of flowers that fell off was 81% so the number of fruits that were formed until they were physiologically ripe was 8. In accordance with the research data obtained, the success of the cross shows that the level of self-cross compatibility is relatively low namely 8%, and it can be concluded that the nature of the cross is incompatible (crosses below 30%).